The Impact of Global Crises on Women: The Case of Covid-19 in Egypt - Dokhan, Nour A. (AUC Knowledge Fountain, 2021)
Any global crisis is expected to affect every human being, but for women it is always twice as hard. In the case of Covid-19, women are more affected across every domain, from social protection to health, simply because if their gender. This research explores the impact of Covid-19 on women, both economically and socially, with the focus on the case of Egypt. It explores the systematic gender inequalities in the economic, social, and health spheres using cases from previous crises, and how this gender inequality and vulnerability has resulted in much worse consequences of Covid-19 than that of men. The primary research focuses on women in upper/middle classes, and aimed to answer, as we emerge from this pandemic, how can we prevent it from excavating the existing gender inequalities? The primary research displayed that the pandemic’s impact was felt deeply and added a strain women, however it is also important to point out that it also portrayed some positive changes especially in household dynamics. Concluding that the imbedded gender stereotypes that add pressures on women are not related to social or economic class, they are deep rooted in society and will only change, if the younger generation change those ideals and recognize the role of women as an active agent in the development process of the society. The research also examined the Egyptian Covid-19 response plan in comparison to other countries and overall, the Egyptian response plan reflected a new gender-sensitive strategy that is very apparent in almost all the policies. Egypt addressed issues like unpaid care work, and increasing in cash benefits to female-headed households, and micro financing to women entrepreneurs, which was not the case for many countries